T3P® -DMSO Mediated One-pot Tandem Approach for the Synthesis of 3,4-dihydropyrimidin-2(1H)-ones/thiones from Alcohols - Vinaya, Kambappa; Shivaramu, Prasanna D.; Chandrashekara, Ganganahalli K.; Chandrappa, Siddappa; Rangappa, Kanchugarakoppal S. (Letters in Organic Chemistry, 2018)
Background: Biginelli reaction is one of the most important multiple-component chemical reactions which creates 3,4-dihydropyrimidin-2(1H)-ones. Even though Biginelli reaction was reported over a century using different substrates, literature lacks the example of the use of alcohols as a substrate. The substitution of aldehyde component with another functional group has not been explored so far. Method: In the present study, we have used Propylphosphonic anhydride (T3P®)-DMSO as an efficient and mild reagent for the one-pot synthesis of 3,4-dihydropyrimidin-2(1H)-ones/thiones from aromatic alcohols. Results: Alcohols are oxidized in situ to aldehydes under mild conditions, which in turn undergo a three-component reaction with β-ketoester and urea/thiourea to afford 3,4-dihydropyrimidin-2(1H)- ones/thiones. Conclusion: The synthesis of 3,4-dihydropyrimidin-2(1H)-ones/thiones directly from alcohols has been reported for the first time under mild reaction conditions in good yield. Easy work up procedure, low cost and less toxicity of the reagent are the main advantages of this protocol.
Keywords: biginelli reaction